Education and gastroenterology fellow knowledge about endoscopic mucosal resection of colon adenomas: a survey-based study - Garg, Shashank; Inamdar, Sumant; Tharian, Benjamin; Muniraj, Thiruvengadam; Aslanian, Harry R. (Endoscopy International Open, 2021)
Background and study aims Endoscopic mucosal resection (EMR) is an effective way to remove large (> 2 cm) colon adenomas. Training about it has not been standardized in fellowship programs. This study was aimed at evaluating the education and knowledge of gastroenterology fellows about EMR of colorectal adenomas.Methods Participation in this survey was offered to 1730 gastroenterology fellows in the United States during the academic year 2019 to 2020. The survey assessed endoscopic mucosal resection training and knowledge and was approved and administered by the American College of Gastroenterology.Results A total of 163 fellows (9.4 %) completed the survey. Only 85 fellows (52.1 %) reported receiving formal education in endoscopic mucosal resection. Fellow confidence was lowest regarding knowing electrosurgery unit settings. Fewer fellows correctly identified Paris 0-IIb (79, 48.5 %; P < 0.0001) or NICE I (114, 69.9 %; P < 0.01) lesions as compared to other Paris and NICE III lesions, respectively. Only 73 (44.8 %) and 93 fellows (57.1 %) arranged steps of EMR in the correct order and identified the correct type of current used for resection, respectively. Training year, male sex, and provision of advanced endoscopy rotations during fellowship were associated with a higher knowledge score for EMR.Conclusions Nearly half of all fellows reported no formal education in EMR and incorrectly ordered its steps. Adenoma assessment by Paris and NICE classifications and electrosurgery unit settings were the most prominent knowledge deficiencies. Incorporation of standardized training about EMR with inclusion of advanced endoscopy rotations appears to be an important educational opportunity during gastroenterology fellowship.